2018
DOI: 10.1029/2017jf004540
|View full text |Cite
|
Sign up to set email alerts
|

Indications of Dynamic Effects on Scaling Relationships Between Channel Sinuosity and Vegetation Patch Size Across a Salt Marsh Platform

Abstract: Salt marshes are important coastal areas that consist of a vegetated intertidal marsh platform and a drainage network of tidal channels. How salt marshes and their drainage networks develop is not fully understood, but it has been shown that the biogeomorphic interactions and feedbacks between vegetation development and channel formation play an important role. We examined the relationships among tidal channel sinuosity, marsh roughness, vegetation type (pioneer, Elymus athericus or Phragmites australis), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 113 publications
(183 reference statements)
1
23
0
Order By: Relevance
“…Lastly, coastal wetlands are among some of the most dynamic and complex ecosystems on the planet. Many different factors, such as seasonal and climate changes, water temperature, altered flooding and salinity patterns, sea-level rise, topography, etc., [11,13], contribute to the current state of the land cover and its physical properties at the time of recording the remote sensing observations. Thus, the authors emphasize that the classification results shown here, based on the classes chosen to be examined, are valid for the specific data set acquired at a certain time over the study site.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lastly, coastal wetlands are among some of the most dynamic and complex ecosystems on the planet. Many different factors, such as seasonal and climate changes, water temperature, altered flooding and salinity patterns, sea-level rise, topography, etc., [11,13], contribute to the current state of the land cover and its physical properties at the time of recording the remote sensing observations. Thus, the authors emphasize that the classification results shown here, based on the classes chosen to be examined, are valid for the specific data set acquired at a certain time over the study site.…”
Section: Discussionmentioning
confidence: 99%
“…Coastal wetland classification is challenging because vegetation and other land cover objects modulate with water level fluctuation and other environmental stressors, leading to sometimes rapid and frequent changes in the type and spatial distribution of a certain land cover [9,10]. The ability to accurately and quickly monitor and predict land cover undergoing rapid and seasonal variations in response to changing environmental factors, including seasonal and climate changes, topography, sea-level rise, water temperature, altered flooding and salinity patterns, etc., [11][12][13], is crucial for updated and/or continuous land cover monitoring systems. Wetland land cover processes as well as other dynamic landscapes are further complicated by the need for frequent data collection methods, and the subsequent demands for faster and automatic algorithms analyzing very high spatial, temporal, and spectral resolution imagery by the monitoring system with the lowest level of human intervention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These validation areas were appositely selected for the visual estimation of cover percentage and a quick classification of the main vegetation typologies like sand-partially vegetated, shrub and herbaceous vegetation, shrubs, and trees. The field observations dataset was integrated by in situ spectral measurements ( Figure 3) with a ViewSpecPRO ® ASD (Boulder, CO, USA) instrument [31,[35][36][37].…”
Section: Field Measurementsmentioning
confidence: 99%
“…where l is the along-foot line length and L is the straight-foot line distance between the starting and ending points [35]. In addition, the profile underlying the surface, a proxy for the sediment volume of the dune, was calculated with the following equation:…”
Section: Step 1: Discrete Pixel-based Analysismentioning
confidence: 99%